The ratio of oxidized and reduced forms of selected antioxidants as a possible marker of oxidative stress in humans - Kanďár, Roman (BMC. Biomedical chromatography, 2016)
Oxidative stress is an imbalance between reactive oxygen species exposure and the ability of organisms to detoxify the reactive intermediates and to repair the oxidative damage of biologically important molecules. Many clinical studies of oxidative stress unfortunately provide conflicting and contradictory results. The ability of antioxidant systems to adequately respond to oxidative stress can be used in laboratory diagnostics. In the present review, methods using the ratio of reduced and oxidized forms of uric acid, ascorbic acid, glutathione and coenzyme Q10 as suitable indicators of oxidative stress are discussed. From the mentioned publications it is evident that suitable sample preparation prior to analysis is crucial.
Keywords: oxidační stres; oxidace-redukce; antioxidancia; biologické markery; Animals; lidé; Oxidation-Reduction; Oxidative Stress; Antioxidants; Humans; Biomarkers; zvířata